PREVENTION OF CHRONIC KIDNEY DISEASE AND CHRONIC HEART FAILURE - Shodikulova Gulandom Zikriyayevna; Muxitdinova Gulshan Zoxirovna; Qahhorova Shohista To’raqulovna (Journals Park Publishing, 2022)
Chronic renal failure (CRF) is a gradual deterioration of kidney function over a long period of time. In modern literature, the term "chronic kidney disease" is found, which has a somewhat broader meaning and implies a decrease in kidney function for three months or more. The function of the kidneys is to maintain a normal balance of fluid and salts in the body, as well as to remove protein metabolism products (nitrogenous slags) from the body, forming urine. With CRF, blood purification does not occur to a sufficient extent, which over time can lead to severe complications. In the early stages of chronic renal failure, no symptoms may occur. The disease is often detected when kidney function deteriorates significantly. Chronic renal failure is a syndrome that occurs against the background of progressive death of nephrons. Because of this, the filtration and excretory functions of the kidneys are gradually disrupted. Over time, such changes cause deviations in the work of all organs and systems. It is possible to recognize developing chronic renal failure by the general symptoms of intoxication: headaches, weakness, nausea, vomiting, swelling.
Keywords: glomerular filtration rate; hypertension disease; the functional state of kidneys